PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPEGUIDED NOTE TAKING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 8 SIJUNJUNG - Marnis, Desi; Delsi K, Delsi K; Cesaria, Anna (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research background by the studentsâ not focus when the teacher explain a matery ability and studentâs understanding of mathematical consept was low, then students lazy to note about subject when the teacher explain it. This research was designed for revealing whether the mathematics conceptual understanding of the students taught by using Guided Note Taking active learning strategy assisted with a quiz was better than that of students taught by using conventional learning in class VIII SMPN 8 Sijunjung. This was an experimental research. Based on the result of data analysis, it was figured out that the studentsâ mathematics conceptual understanding kept improving from a meeting to the next one. In addition, the result of hypothesis test showed that P-value (0,005) was smaller than Â = 0,05 indicating that the hypothesis was accepted on 95% of realibility. Based on the result, it was concluded tha the mathematics conceptual understanding of the students taught by using Guided Note Taking active learning strategy assisted with a Quiz was better tha that of students taught by using conventional learnig. Â